Exclusive Breastfeeding Support to Increase Exclusive Breastfeeding at Muhammadiyah Gresik Hospital - Hamidah, Siti (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The first 1000 days of life is a critical period, exclusive breastfeeding and infant stimulation are important. The purpose of the study was to analyze the effectiveness of Communication, Information and Education (CIE) on: (1) the mother's knowledge about exclusive breastfeeding, (2) breast care, (3) how to breastfeed correctly, (4) mother's attitude in exclusive breastfeeding. The research design was quasi experimental with pre-post test group intervention. The research time was 8 months, from August 2022 to March 2023. The dependent variable was the provision of CIE by Aisyiyah cadres and the independent variables were 1) mother's knowledge about exclusive breastfeeding, (2) breast care, (3) the correct way of breastfeeding, and (4) mother's attitude. The sample was quota sampling, totaling 100 subjects. The data collection technique used a pre questionnaire given directly during the first or second post partum day and a post questionnaire given after 6 months through visits and MCH books. Data analysis found that mothers' knowledge about breast milk and breastfeeding before and after CIE showed an average value increased from 56.68 to 90.12. The mean value of breast care skills before and after the CIE was 41.24 and 88.48. The mean value of breastfeeding skills before and after the CIE was 43.64 and 88.46. The mean scores of maternal attitudes before and after the CIE were 63.61 and 90.27. Breastfeeding success rate was 91%. The effectiveness of CIE using the Wilcoxon analysis test, shows; there is effectiveness of CIE on knowledge of breast milk and breastfeeding (p<0.05), the value of negative ranks (decrease) is 0. The value of positive ranks (increase) is 50.50. Likewise, the effectiveness of CIE on breast care skills, the effectiveness of CIE on correct breastfeeding skills, and the effectiveness of CIE on maternal attitudes showed the same value (p<0.05), the value of negative ranks (decrease) was 0. The value of positive ranks (increase) was 50.50. The value of ties (equal) is 0.